Influence of notched baffles on aerothermal performance behaviors in a channel - Phila, Arnut; Keaitnukul, Warin; Eiamsa-ard, Smith; Naphon, Paisarn; Maruyama, Naoki; Hirota, Masafumi; Chuwattanakul, Varesa (My University, 2023)
The proper designs of modified heat transfer surfaces or turbulence enhancement inserts for heat transfer augmentation are extremely important for improving overall aerothermal performances relating to the energy-saving capabilities of thermal systems. A major challenge is to control friction loss as little as possible while maintaining reasonable heat transfer enhancement. Transverse baffles with rectangular notches or notched baffles (NBs) were applied for improving aerothermal performance in a channel with a constant aspect ratio of 3.75 while notch height-to-baffle height ratio (a/e) ranged from 0.125 to 0.5. Reynolds number ranged from 6000 to 24,000, in experiments. Heat transfer enhancement, pressure loss, and aerothermal performance in a rectangular channel with notched baffles were examined. Compared to the solid transverse baffle (SB, a/e = 0), the NBs with a/e = 0.125 increased the heat transfer rate while lessening the pressure loss, as shown by the experimental findings. Obviously, Nusselt number, friction factor and aerothermal performance increased as the a/e ratio decreased. The NBs with the smallest notch height-to-baffle height ratio (a/e = 0.125) exhibited the highest aerothermal performance of 1.17, which can be attributed to the efficient heat transfer enhancement by the strong multi-jet impingements and the moderate friction loss penalty resulting from the presence of notches (spaces) on the baffles.
Keywords: Channel; Heat transfer enhancement; Notched baffle; Solid baffle; Transverse baffle